Parents' experiences of requests for organ and tissue donation: the value of asking. Issue 9 (11th September 2019) - Darlington, Anne-Sophie; Long-Sutehall, Tracy; Randall, Duncan; Wakefield, Claire; Robinson, Victoria; Brierley, Joe
Abstract : Objective: A proportion of children die, making them potentially eligible to be organ/tissue donors. Not all are approached for donation, and experiences of those parents are not well understood. The objective was to investigate to what extent organ and tissue donation (OTD) is discussed as part of end-of-life care and to explore parents' and healthcare professionals' (HCPs) experiences. Design: A retrospective qualitative study. Setting: Multicentre study with participants recruited through two neonatal intensive care units (ICUs), two paediatric ICUs, a cardiac ICU and a children's hospice. Patients: Bereaved parents, parents of a child with a long-term condition (LTC) and HCPs. Interventions: None. Main outcomes and measures: Parents' and HCPs' views and experiences of discussions about OTD. Results: 24 parents of 20 children were interviewed: 21 bereaved parents and 3 parents of a child with a LTC. Seven parents were asked about donation (13 not asked), four agreed and two donated. 41 HCPs were interviewed. Themes: complexity of donation process, OTD as a coping strategy, the importance of asking, difficulty of raising the topic, and parents' assumptions about health of organs (when donation is not discussed). Conclusions: The findings add new knowledge about parents' assumptions about the value of their child's organs when discussions about OTD are not raised, and that HCPs do not routinely ask, are sometimes hesitant to ask in fear of damaging relationships, and the reality of the complexity of the donation process. Given the current levels of awareness around OTD, the topic should be raised.